Advances in Ferroptosis and Inflammatory Bowel Disease - PU Yu, ZHANG Jixiang, DONG Weiguo (Zhongguo quanke yixue, 2023)
Inflammatory bowel disease (IBD) is a group of chronic non-specific gastrointestinal inflammatory conditions, whose pathogenic factors and pathogenesis may be related to environmental factors, genetic susceptibility, gut microbiota and immune responses. Ferroptosis is a newly found cell death caused by the accumulation of iron-dependent lipid hydroperoxides, which is tightly regulated by a lipid repair system including glutathione (GSH) and glutathione peroxidase 4 (GPx4). Increasing studies have reported the fundamental features of ferroptosis in the injured gastrointestinal tract in IBD patients, including iron deposition, GSH exhaustion, GPx4 inactivation, and lipid peroxidation. Furthermore, regulating the key ferroptosis-related genes may alter the progression, severity, or even morbidity of IBD. We reviewed the basic mechanism of ferroptosis, and the prospect of ferroptosis pathways as therapeutic targets in IBD. In addition, the initiation of ferroptosis for improving IBD by extrinsic (transporter-dependent) or intrinsic (enzyme-regulated) pathway, may be a new direction for clinical treatment of IBD.